Why Are Canadian Banks More Resilient? - Huang, Rocco (IMF Working Papers; Working Paper ;, 2009)
This paper explores factors behind Canadian banks' relative resilience in the ongoing credit turmoil. We identify two main causes: a higher share of depository funding (vs. wholesale funding) in liabilities, and a number of regulatory and structural factors in the Canadian market that reduced banks' incentives to take excessive risks. The robust predictive power of the depository funding ratio is confirmed in a multivariate analysis of the performance of 72 largest commercial banks in OECD countries during the turmoil.